IMPLEMENTING THE CHRONIC DISEASE SELF-MANAGEMENT PROGRAM IN RURAL AND REMOTE AREAS. (11th November 2018) - Longstreth, M; Duhamel, D; Carrico, C; Barry, R; McKibbin, C
Abstract: Self-management programs are widely recommended to empower participants, increase their confidence, and teach skills and techniques to enable them to better manage their chronic health conditions. Some important work has been done to examine the effect that delivering CDSMP via telehealth has on health outcomes. At the same time, information is still needed about the value of traditional CDSMP for improving key health outcomes in rural and remote areas. This uncontrolled study examined change in behavioral, psychosocial, health, and service outcomes following the 6-week CDSMP intervention attended by adults and older adults residing in a rural and remote state. Fifty participants completed both pre- and post-intervention evaluations. Data were analyzed using paired sample t-tests. Alpha was set to p<.05. CDSMP resulted in significant reductions in depressive symptoms (t[49]=2.40, p=0.020) and significant improvements in self-efficacy (t[49]=2.89, p=0.006). No differences were found in behavioral outcomes or in health and service outcomes, such as physical activity behavior, quality of life, or hospital service use. CDSMP, implemented in-person in rural and remote communities, appears useful for improving participants' confidence in their ability to self-manage chronic health conditions and for reducing their depressive symptoms. A larger sample with longer follow up may provide additional information about the value of this intervention on behavioral, health, and service outcomes for rural and remote older adults. Further qualitative examination of rural and remote older adults' experiences of barriers and facilitators of change in relation to CDSMP is warranted.